Identity destabilised : living in an overheated world - Eriksen, Thomas Hylland; Schober, Elisabeth (Pluto Press, 2016)
We are living in a new epoch: the Anthropocene, where the world is overheated by human activity, driven too fast and filled too full, uneven and unequal. This collection explores the question of identity in this new world, looking at the consequences of rapidly accelerating change on social and personal identities and providing a concrete set of perspectives on how people conceive their selves and belonging in the twenty-first century. Featuring examinations of the Phiippines, Israel, Australia, the Cape Verde Islands, and Afghanistan, the book studies changes generated by rapid industrialization, forced return of migrants, sudden population growth, and the touristification of local cultures. --